PEMBELAJARAN PAI ERA COVID-19 DI RANTAUPRAPAT, KABUPATEN LABUHANBATU - Leli Hasanah Lubis (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2020)
Learning Religion (Islam) is the primary need of children in the scientificaspect. The morality and morals of children are more or less formed through IslamicEducation learning that they receive from parents, teachers, society and adults. Forthis reason, PAI learning is still needed by children in any condition, including theCovid-19 era. This paper aims to analyze the learning of PAI in the Covid-19 erain RanntauPrapat,kabupaten Labuhanbatu. The formulation of this study focuseson discussing how learning methods, teaching objectives, learning objectives andmaterials provided by educators during the Covid-19 era in RantauPrapat,KabupatenLabuhanbatu. The data was collected using a qualitative approach using field studymethods (observation, interviews, documentation). The results of this study foundthat (1) the learning method was carried out by discussion, question and answer,and inviting students to study at the teacher’s house; (2) learning objectives so thatchildren continue to receive religious advice through Islamic Education learning;(3) learning objectives are aimed at elementary age children; and (4) the materialtaught is a combination of the content of the PAI curriculum and local wisdom in theRantauPrapat,Labuhanbatu